Revision of Neacomys spinosus (Thomas, 1882) (Rodentia: Cricetidae) with emphasis on Peruvian populations and the description of a new species - Hurtado, Natali; Pacheco, Víctor (Zootaxa, 2017)
The large spiny mouse Neacomys spinosus (Thomas, 1882) has been considered the widest ranging species of the genus, occurring in southern Colombia, eastern Peru, western Brazil and northern Bolivia. The morphological variation between subspecies and populations of N. spinosus has been noted; nonetheless, this variation has not been assessed in a morphological or molecular context. Here, we present a taxonomic revision of Neacomys spinosus s.l. using qualitative and quantitative morphological analyses. These analyses were complemented with molecular analysis to reconstruct the phylogenetic relationships among species of Neacomys, based on sequences of the cytochrome b gene. Our results reveal that N. spinosus s.l. is a monophyletic group, and morphological and molecular evidence to differentiate three taxa: N. spinosus s.s., an endemic species from mountain cloud forests in Peru; N. amoenus s.l. from the Cerrado between Bolivia and Brazil to the Amazonia between Ecuador and northern Peru, and Neacomys sp. nov. from mountain cloud forests from southern Peru to Bolivia. Also, our molecular results indicate that Neacomys is still far from being completely known. For instance, there are three candidate species pending of taxonomic revision. Finally, we propose three species groups within Neacomys: “paracou”, “tenuipes” and “spinosus”, and discuss biogeographical scenarios of the genus within South America.